2012
DOI: 10.1016/j.pain.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

No pain no gain? Pursuing a competing goal inhibits avoidance behavior

Abstract: This experiment investigated pain-related avoidance behaviour in a context of competing goals. Participants (N = 56) were presented trials of two different tasks of which one could produce pain. They were free to decide whether or not to perform trials of these tasks. In half of the participants a competing goal was activated by instructing them that they would receive a monetary reward corresponding to the number of pain task trials actually performed (competition group). In the other half of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 48 publications
10
58
1
2
Order By: Relevance
“…This finding is however in line with other studies showing that introducing a monetary incentive does not necessarily result in a decrease in painrelated fear. 29,49 The current study extends available evidence for the inclusion of a motivational perspective on avoidance tendencies and behavior, wherein the dynamics of several−possibly conflicting−goals should be considered. Avoidance behavior is considered a relatively stable response driven by a fear-based motivation to prevent further injury.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This finding is however in line with other studies showing that introducing a monetary incentive does not necessarily result in a decrease in painrelated fear. 29,49 The current study extends available evidence for the inclusion of a motivational perspective on avoidance tendencies and behavior, wherein the dynamics of several−possibly conflicting−goals should be considered. Avoidance behavior is considered a relatively stable response driven by a fear-based motivation to prevent further injury.…”
Section: Discussionsupporting
confidence: 56%
“…9,18,29,54 However, the results of the current study show that avoidance can be influenced by the presence of concomitant, competing goals, such as the goal to retrieve a reward, even without changing pain-related fear itself. 23,40,44,47,49 Thus, avoidance behavior may vary from situation-to-situation, also even within individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both experimental studies and research in naturalistic settings are needed to test the validity of these ideas. For example, in previous studies it was found that the goal of obtaining a financial reward increased task persistence during experimental pain 66 , suppressed attention to pain-related cues 58 , and even reduced pain perception in high pain catastrophizers 59 . It would be interesting to extend this line of research by manipulating the type of motivation with which task goals are pursued.…”
Section: Goal Content or Type Of Motivation?mentioning
confidence: 99%
“…Current models insufficiently address the question how patients try to function despite pain. In a recent experimental study, it was demonstrated that the decision to avoid or persist a pain-provoking task, is strongly affected by the motivational context 66 . Healthy volunteers were offered the choice to perform or avoid trials from a pain-provoking task.…”
Section: Capturing the Dynamics Between Personal And Contextual Factorsmentioning
confidence: 99%